2017
DOI: 10.1016/j.jcjo.2017.02.025
|View full text |Cite
|
Sign up to set email alerts
|

A decade of surgical eye removals in Ontario: a clinical-pathological study

Abstract: A blind painful eye and neoplasms were the most commonly documented indications prior to removal of the eye. Common pathologies included glaucoma, neoplasms, infection/inflammation, and trauma. However, regardless of the primary cause, glaucoma-related pathologies were the most common pathologic findings. Refractory eye disease and pain continue to be important reasons for removal of eyes among patients in Ontario. More effective and targeted management strategies are needed to reduce the need for this radical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
0
8
2
Order By: Relevance
“…A follow-up study covering 1992–2004 identified 56 enucleations, with the commonest indication being trauma followed by tumour 4 . A Canadian study of 713 eyes received over a 10-year period (60% of which were enucleations) found the commonest indication to be blind painful eye (37%) with slightly fewer tumours (35%) 5 …”
Section: Discussionmentioning
confidence: 99%
“…A follow-up study covering 1992–2004 identified 56 enucleations, with the commonest indication being trauma followed by tumour 4 . A Canadian study of 713 eyes received over a 10-year period (60% of which were enucleations) found the commonest indication to be blind painful eye (37%) with slightly fewer tumours (35%) 5 …”
Section: Discussionmentioning
confidence: 99%
“…[28] found a high percentage of malignant tumours of 27% in their Copenhagen study population, compared to ndings by de Gottrau et al [29] in Erlangen (19.6%), Saeed et al [30] in Leeds (19%) and our own data from the Freiburg region (18%), during comparable time ranges. Even more pronounced was the percentage of malignant tumours in Atlanta in 1995 (30.8%) [17] and in Toronto 2004-2013 (36%) [32]. We assume that referral patterns may have played a signi cant role, as ocular tumour cases were referred to specialized tertiary care centres for intraocular tumours, such as in Copenhagen [28], Atlanta [17] and Toronto [32].…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Even more pronounced was the percentage of malignant tumours in Atlanta in 1995 (30.8%) [17] and in Toronto 2004-2013 (36%) [32]. We assume that referral patterns may have played a signi cant role, as ocular tumour cases were referred to specialized tertiary care centres for intraocular tumours, such as in Copenhagen [28], Atlanta [17] and Toronto [32].…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients presenting phthisis bulbi with history of ocular neoplasia, eye enucleation (EE) appears to be one of the possible options to insure better facial appearance and pain relief [3]. EE involves the complete removal of the eye's contents and the scleral shell preserving the extraocular muscles.…”
Section: Introductionmentioning
confidence: 99%